IMPLIKASI HUKUM BAGI UMKM PASCA PENETAPAN PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG (PERPU) TENTANG CIPTA KERJA SEBAGAI UNDANG-UNDANG - Hidayat, Mohamad Mulky; Huda, Miftakhul (Fakultas Hukum Universitas Narotama, 2024)
Micro, Small and Medium Enterprises are the pillars of the community's economy. In order to achieve stable and sustainable economic growth, it is necessary to support strong economic stability. Before the Job Creation Law was passed, which was later replaced by the Job Creation Perpu, there were still many obstacles and barriers faced by business actors, especially in micro and small businesses, including disharmonization of business licensing procedures for micro and small businesses between the law and its implementing regulations so that requires a lot of time and money. To deal with these conditions, government support is urgently needed, including in the form of establishing laws and regulations that favor micro and small businesses. With the ratification of Perpu Number 2 of 2022, which provides many conveniences for micro and small businesses and increases efficiency for business actors, it is hoped that it can become a guideline for micro and small businesses to further grow, develop and compete in the global and free market era. So as to balance the portion of large, medium, and especially micro and small businesses, while creating a fair business climate and fairness for MSMEs throughout Indonesia to a much greater extent. Keywords: Job Creation Law, MSMEs, Licensing